Strategies for improving ESP learners’ language skills - Indasari, Nur Laili; Fajriyah, Latifatul; Rosyidi, Ali (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
In this era of globalization, the demand for ESP instruction is increasing. ESP instructors must develop instruction suitable to the student's needs. This research aims to explore the strategies of the lecturer in teaching ESP students, to acknowledge the improvement in English language skills, and to gain the students’ perceptions of the implemented strategies. The participants are the lecturer and the students who take Early Childhood Islamic Education and Islamic Elementary School Teacher Education programs. This research used classroom action research design. The data were obtained by observing the ESP instruction implemented during the learning process, pre and post-tests, and the students’ responses. The results of the study revealed that ESP instructions or strategies used by the lecturer improved the English skills of students such as ability in speaking, pronunciation, and language use.  The students’ perceptions of the strategies were also positive. They viewed that these strategies helped them understand the learning concept. Overall, the implementation of these strategies led to enhanced student learning outcomes and proficiency in English speaking skills.